Stakeholders and managerial practices in basic public school: A multi-case study - Singh, Ananda Silva; Freitas, Vanyne Aparecida Franco; Valadão Junior, Valdir Machado (Education Policy Analysis Archives, 2019)
The stakeholder approach has been, since the decade of 1980, one of the most relevant theories to understand the relationship that is established between the different groups that intertwine in everyday’s managerial practices of an organization. Such theory is relevant to comprehend school’s managerial process, since schools are constituted by stakeholders who long for their expectations to be met. This study aims at understanding how managerial practices of basic public schools, in relations with their interest groups (principal, supervisors, teachers, pedagogues, general service assistant, administrative officers, patrimonial agents, students’ parents), take place. A multicase study was carried out in four schools, data were collected from documents, direct observation and evaluated by means of the content analysis technique, based on categories from Chanlat’s (1996) participative management. Some findings were: (i) some stakeholders didn’t know or participated in school management, (ii) the need to engage the community to access resources, (iii) conflicting goals regarding stakeholders and the school, (iv) the need to strengthen the communication among stakeholders to make the control and evaluation system more effective, (v) how it’s necessary to engage stakeholders in the managerial process to obtain certain advantages.